The emergence of Australia's electricity market. (14th January 2008) - Moran, Alan
The Australian energy market has developed in response to two sets of government decisions. The first was a policy of the Victorian Government to sell its state-owned electricity supply system and to do so in a way that introduced competition wherever this was possible. At the same time, the Commonwealth (federal) Government had determined on a course of introducing competitive provision of electricity, without any commitment to privatisation. The outcome has been a considerable increase in productivity and reliability accompanied by price reductions. Issues that remain include ensuring the provision of adequate transmission where this is regulated and competing with local regulation, the provision of which is market-determined. There is also a potentially unstable coexistence of private- and government-owned generation, with the latter appearing to be responsive to government policies that might jeopardise market-driven supply augmentations. Australia is also wrestling with responses to carbon emissions, which might create future investment uncertainties.